Poisonous Pedagogy: Patriarchal Religious Tenet of Child Illegitimacy in Nawal El- Sadaawi’s The Fall of the Imam - Alimi, Nurayn Fola (NIU Journal of Humanities, 2025)
This paper interrogates the interconnection of religion, patriarchy and child illegitimacy in Nawal El Saadawi’s The Fall of the Imam . In Islam, Zina laws are part of the jurisprudence that give cogency to the phenomenon of child (il)legitimacy and the criminalisation of female sexuality. Thus, juristic terminology, Waladul zina designates the illegitimate child as a product of fornication. Even though a child belongs to the one in whose bed it is conceived, the legitimacy of a child is tied to the nuptial bed in Islamic law. Focusing on the prism of the novel’s narrative of the subject matter of religion, patriarchy and female sexuality, the paper interrogates the concern with the phenomenon of child illegitimacy. A qualitative textual data collection from the novel is employed to interrogate and discuss the contradictions underscoring the interconnections of religion, patriarchy and female sexuality in a fictional Islamic society. Textual data analysis is anchored broadly on Marxist and Feminist literary dialectics. The concepts of ‘’feminism’’, ‘’patriarchy’’ and ‘’ideology’’ are understood and deployed in the context of the religious sentiments and the established religious ethos which define the superstructure of the setting of the novel. Critical literary analysis revealed that, in Nawal El Sadaawi’s The Fall of the Imam , male characters manipulate the religious tenets of Islam, use these tenets as poisonous pedagogy to execute personal, political and gender biases agenda. The paper concludes that the novel carpets the politics of gender by regarding it as a constitutive religious discourse and ascertains that Islam is a political agency for executing and maintaining traditional male dominance and gender disparities in the Arab society. Keywords: Illegitimacy, Patriarchy, Girl-Child, Waladu Zina , Islam, Criminalisation